THE USE OF PEER FEEDBACK TECHNIQUE IN IMPROVING STUDENTS' NARRATIVE WRITING (A Quasi Experimental Study at One SMAN in Cimahi) - Puteri Lenggogeni, - (2011)
This research investigated the use of peer feedback technique in improving students' narrative writing. The study employed a quasi experimental design with two classes of ten graders at one SMAN in Cimahi as the sample. The data were obtained through a pre-test, post-test and questionnaire. The data gathered through pre-test and post-test were computed one by one using IBM SPSS Statistics 19.0 for Windows while data from questionnaire were analyzed based on the frequency of students' answers and then were calculated and interpreted into percentage. The result of the study showed that the experimental group had better writing skill. The statistical computation showed that peer feedback technique was likely to be effective in improving students' narrative writing (tobt2.296>tcrit2.000, r= 0.73). Moreover, the data from questionnaire showed that peer feedback technique was positively responded by the students. Based on these findings, it is recommended that peer feedback technique be applied in teaching writing. The teacher may try to take advantage of peer feedback technique to be utilized in their classroom activities to conduct an effective and interesting learning atmosphere.